Introduced banana hybrids in Africa: seed systems, farmers' experiences and consumers' perspectives - Karamura, E.B.; Tinzaara, William; Kikulwe, Enoch Mutebi; Ochola, D.; Ocimati, W.; Karamura, D. (International Society for Horticultural Science, 2016)
Over the past three decades, more than 40 banana cultivars have been introduced in eastern and southern Africa for evaluation and dissemination to smallholder farmers facing banana productivity challenges. This study analyses the seed systems used to avail the genotypes to the target users, discusses farmers' experiences and consumers' perspectives in five countries NDASH Kenya, Mozambique, Tanzania, Rwanda and Uganda. The study reveals that materials came from the International Transit Centre as tissue culture plantlets (rooting or proliferating), from private companies such as Du Roi, South Africa and from the national and international breeding programs such as NARO-Uganda and International Institute of Tropical Agriculture. Within the countries, new genotypes followed both the formal and informal seed systems. Of the 44 genotypes introduced, 18 were not adopted and the adoption of the others depended on the end users' socioeconomic perspectives. For green-cooking bananas, farmers selected for sensory attributes (taste, flavor, texture, color of the food when cooked). For dessert bananas targeting local and regional markets, in addition to sensory attributes, farmers selected for bunch, hand and finger characteristics plus similarity with other traditional dessert cultivars. The selection for juice/beer/wine cultivars focused on astringency, starch, plant vigor and bunch size. Irrespective of the end use, resistance to pests and diseases and early maturation were important considerations. Analysis showed that sensory attributes significantly contributed to the consumers' willingness to pay for new cultivars. Farmers explored new uses and two cultivars were adapted to new uses while another two were adapted to new consumer markets. It is suggested that by involving the end users in the evaluation and selection of new cultivars (participatory variety selection, PVS) adoption of introduced cultivars would be enhanced.